Effects of different blends of protein sources as alternatives to dietary fishmeal on growth performance and body lipid composition of Atlantic salmon (Salmo salar L.) - Pratoomyot, Jarunan; Bendiksen, Eldar Asgard; Campbell, Patrick; Jauncey, Kim; Bell, J Gordon; Tocher, Douglas R (Aquaculture, 2011)
Recently, we reported that growth of Atlantic salmon was reduced as dietary fishmeal (FM) was lowered from 25 % to 5 % in dual-substituted feeds compared to a control diet, formulated to represent the current upper levels of substitution of FM and fish oil. In the present study, the effects of different alternative protein blends and binders on growth of salmon fed dual-substituted feeds containing only 11 % FM, and with 60 % of dietary fish oil replaced by rapeseed oil were investigated. Salmon of initial weight 1.3 kg were grown to market size (> 3 kg) over a period of 19 weeks. Salmon fed the diets with reduced FM showed lower final weight, SGR and TGC, associated with reduced feed intake. There was a tendency for increased FCR in fish fed the diets containing reduced FM although this was not significant, and there was no effect on PER. There were no significant effects on digestibility of protein or fat but the two parameters varied reciprocally and there were clear trends of increased protein and lower fat digestibilities in fish fed diets with reduced FM. Although lipid and fatty acid compositions did not vary greatly between diets there were significant effects on fish tissue compositions. Thus, liver lipid was generally reduced in fish fed diets with lower FM, significantly so in two of the four treatments. The proportions of monoenes were significantly lower and those of polyunsaturated fatty acids (PUFA) significantly higher in flesh and liver of fish fed diets with reduced levels of FM. The increased proportions of PUFA were due to increased percentages of 20:4n-6, 20:5n-3, 22:5n-3 and, although not consistently significant, 22:6n-3. The mechanisms for these unexpected effects of diet on tissue lipids and fatty acids are discussed.